THE INFLUENCE OF ONLINE QUIZIZZ LEARNING MEDIA ON CLASS V SOCIAL SCIENCE LEARNING AT SDN DR. SUTOMO V/327 SURABAYA - Febriana Nur Cahyaningrum; Danang Prastyo (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The purpose of the written research is to obtain results on the effect of implementing the online learning media Quizizz on the subject of social studies on economic activity for class V at SDN Dr. Sutomo V/327 Surabaya. Researchers can find out the learning outcomes of students in applying the online learning media Quizizz on social studies in elementary schools. Researchers can find out and see students' responses in using the online learning media Quizizz on social studies in elementary schools. Written research is a descriptive quantitative research. The population used was students of SDN Dr. Sutomo V/327 Surabaya with a sample of class V students. The method used was a test and questionnaire. According to the results of the study processed using SPSS 22, the use of the online learning media Quizizz which acts as a web-based formative assessment media has a significant influence on the progress of student learning outcomes on the material of the periodic system of elements. With the online learning media Quizizz, the process of taking grades is not boring, not monotonous, and can provide comfort to students, so that it encourages enthusiasm in doing quizzes so that student learning outcomes are good.